Pengaruh Pendekatan Matematika Realistik Indonesia Terhadap Pemahaman Konsep Penyajian Data Peserta Didik Kelas V SD. - Yolana, Ulfa; Fitria, Yanti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
The purpose of research is to know the influence of Indonesian Realistic Mathematics Education approach (PMRI) towards the understanding of the concept of data presentation learners in class V elementary school Gugus 1 West Padang, Padang city on 2018/2019 school year. The research is a Quasi Ekspermental Design. The data analysis technique used is t-test. Based on the results obtained by the average value postest understanding of the concept of presenting data by using PMRI approach in the experiment group is 90.37 and control group using conventional learning is 75, 67. This means the experimental group was higher than the control group. From the result of calculation of t t-test obtained Tcount 3.0561 while the T-table with a significant status of 0.05 and df = 32 is 1.69389. Means Tcount > Ttable so that Ha is accepted. Thus, there is a significant influence of Indonesian Realistic Mathematics Education approach for understanding of the concept of presenting data in class V elementary school.Keywords: Indonesian Realistic Mathematics Education Approach, Concept Training